Wigner function based propagation of stochastic field emissions from planar electromagnetic sources - Gradoni, Gabriele; Arnault, Luk R.; Creagh, Stephen C.; Tanner, Gregor; Baharuddin, Mohd Hafiz; Smartt, Christopher; Thomas, David W.P. (Institute of Electrical and Electronics Engineers, 2017)
Modelling the electromagnetic radiation from modern digital systems – acting effectively as extended, stochastic sources as part of a complex architecture – is a challenging task. We follow an approach here based on measuring and propagating field-field autocorrelation functions (ACFs) after suitable averaging. From the modelling side, we use the Wigner transform of the ACFs to describe random wave fields in terms of position and direction of propagation variables. An approximate propagator for the components of the radiated magnetic field is constructed for these ACFs based on a linear flow map. Field-field ACFs at aperture level are obtained from scanning measurements of complex sources. Distance and spatial resolution of the scanning plane is less than a wavelength from the source plane to capture the imprint of evanescent waves in the nearfield ACFs. Near-field scanning and efficient near-to-far field propagation is carried out and compared with measurements. Results of this study will be useful to assist far-field predictions, source reconstruction, and emission source microscopy.